Dual Pathways to Loyalty: How Rational and Affective Factors Shape Revisit Intention in Sports Health Applications - Yang, Jiafa (International Journal of Humanities and Social Science, 2026)
Objective: Amidst the swift evolution of mobile health, sports applications (Sapps) play a vital role in fostering wellness, yet they struggle with substantial user loss. This research explores the underlying psychological factors that drive users’ intention to return to these platforms. Methods: Integrating the Technology Acceptance Model (TAM) and Expectation Confirmation Theory (ECT), a conceptual framework was developed featuring variables such as perceived ease of use, usefulness, trust, cost, and entertainment, alongside usage habits and satisfaction. Data were gathered from 358 university students in Seoul via convenience sampling. Statistical validation and hypothesis testing were performed using SPSS 28.0 and AMOS 28.0 through confirmatory factor analysis (CFA) and structural equation modeling (SEM). Results: Empirical evidence suggests that perceived usefulness is positively predicted by expected confirmation and ease of use. These three elements, in turn, serve as significant antecedents of user satisfaction. Furthermore, while satisfaction, usefulness, and entertainment significantly bolster revisit intention, perceived cost functions as a major inhibitor. However, the direct links between revisit intention and both usage habits and perceived trust were not statistically significant. Conclusion: The decision to reuse Sapps is a combined outcome of cognitive assessments (satisfaction and usefulness) and emotional experiences (entertainment), though it is tempered by cost considerations. These results offer strategic insights for the long-term viability of digital health interventions.